Intervention publique versus régulation professionnelle - Amandine Rauly (Revue de la Régulation)
In 2009 the HPST law entails measures that break with past trends in the practice of telemedicine. This practice refers to any medical procedure remotely using ICT, and it is marginally practiced until 2009. Informal networks intend to reduce the impact of spatial inequalities in medical demography. But legal recognition of telemedicine and its introduction into the HPST law enable it to become a tool for public health policy. This technology should actually allow medical action standardization and thus encourage physicians to reduce their deviant behavior. Expenditure supervision and care quality improvement become the creed of telemedicine policy. To do this, new organizational and technological devices are established and alter production relations and medical care hierarchy. These changes induce conflicts that freeze the deployment of telemedicine until a new institutional compromise emerges.